Metallophosphide poisoning, a rising public health problem in Ethiopia: a systematic review and meta-analysis - Kassaye Demeke Altaye; Bethelhem Yenenew Assefa; Adina Worku Teka; Saron Mulugeta Worku; Geta Bayu Genet; Bikis Liyew; Nahom Worku Teshager (BMC Emergency Medicine)
Abstract Introduction Metallophosphide poisoning, mainly due to aluminum phosphide and zinc phosphide, is a growing public health problem in developing countries associated with a high mortality rate, including in Ethiopia, where it is used a fumigant for stored grains and agricultural commodities. Ethiopia lacks a well-organized poison control center, making it difficult to obtain primary data on metallophosphide poisoning cases and outcomes. This systematic review and meta-analysis aim to determine the pooled prevalence and mortality rate from metallophosphide poisoning in Ethiopia. Methods As of August 2024, PUBMED, EMBASE, SCOPUS, and GOOGLE SCHOLAR were inclusively searched. Two independent reviewers extracted the data. Quality was assessed using the Modified Newcastle-Ottawa Scale adapted for cross-sectional studies. A random effects model was used to obtain the pooled estimate of the prevalence of and mortality rate from metallophosphide poisoning. Results Fourteen studies with a sample size of 3218 were included in the final estimate. The pooled prevalence of metallophosphide poisoning in this systematic review and meta-analysis was 38% (95% CI: 0.14–0.71, I2 = 96.6%, p < 0.0001). In the teen-included studies for the pooled mortality analysis, the sample size was 677 and the pooled mortality rate was 37% (95 % CI: 0.22, 0.55, I2 = 87.8%, P < 0.0001). Conclusion We found a high pooled prevalence of metallophosphide poisoning in Ethiopia. This highlights the urgent need for regulatory actions to restrict the sales and distribution of these substances. This is supported by international experiences from similar low-resource settings. We recommend safer alternatives to control insects and rodents, such as mechanical rodent controls and integrated pest management. Public awareness creation and enhancing local management protocols to reduce the burden and improve the outcome of metallophosphide poisoning.